2020
DOI: 10.1177/1758835920937425
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of systemic immune-inflammation index in colorectal cancer: a meta-analysis

Abstract: Background: Previous studies on the systemic immune-inflammation index (SII), which is based on platelet, neutrophil and lymphocyte counts, as a prognostic marker in patients with colorectal cancer (CRC) yielded inconsistent results. The aim of this study was to evaluate the prognostic and clinicopathological role of SII in CRC via meta-analysis. Methods: A comprehensive literature survey was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 43 publications
(152 reference statements)
5
53
0
Order By: Relevance
“…17 Many studies have demonstrated that there is a close relationship between high SII and increased risk of distant metastasis, poor survival and poor prognosis in patients with colorectal cancer. 8,[18][19][20][21] Chen et al reported that high preoperative NLR (>2.7), PLR (>210) and SII (>340) were associated with poor OS in a study on 1,383 patients with stage I-IV colorectal cancer, who had undergone radical surgery. 22 In a multivariate Cox regression analysis in the same study, inflammatory markers SII (HR: 3.163, 95% CI: 2.616-3.824) and PLR (HR: 1.294 95% CI: 1.123-1.492) were found to be independent predictive factors of OS; and SII (HR: 2.717, 95% CI: 2.287-3.228) was found to be an independent predictive factor of DFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Many studies have demonstrated that there is a close relationship between high SII and increased risk of distant metastasis, poor survival and poor prognosis in patients with colorectal cancer. 8,[18][19][20][21] Chen et al reported that high preoperative NLR (>2.7), PLR (>210) and SII (>340) were associated with poor OS in a study on 1,383 patients with stage I-IV colorectal cancer, who had undergone radical surgery. 22 In a multivariate Cox regression analysis in the same study, inflammatory markers SII (HR: 3.163, 95% CI: 2.616-3.824) and PLR (HR: 1.294 95% CI: 1.123-1.492) were found to be independent predictive factors of OS; and SII (HR: 2.717, 95% CI: 2.287-3.228) was found to be an independent predictive factor of DFS.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although contradictory results have been reported regarding the prognostic significance of systemic immune-inflammation index (SII), which is calculated on the basis of neutrophil, platelet and lymphocyte counts, and is defined as a novel marker compared to other inflammatory markers, a recent meta-analysis reported a relationship between high SII and poor prognosis. 8 Another marker reported to be useful in predicting the prognosis of patients with colorectal cancer is the prognostic nutritional index (PNI), which is calculated on the basis of inflammatory parameters and albumin value. 9 It has been reported that inflammatory markers and the changes observed in them during nCRT can predict pCR in patients with LARC.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies only indicated the preoperative value and the results were not consistent. Some studies indicate that SII was proposed as a significant prognostic factor in CRC [ 21 , 22 , 30 ], whereas other studies were not significant [ 23 , 31 ]. Few studies focused on the changes of inflammatory markers before and after treatment, which might reflect the correlation between the host's inherent inflammatory state and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…There is little previous evidence regarding the prognostic value of neutrophil counts, as most studies have not evaluated neutrophil count as a single independent factor. Its prognostic value has primarily been evaluated using neutrophil-containing parameters, such as NLR, SII, or neutrophil–albumin ratio (NAR) ( 3 , 13 , 14 ). Our previous study demonstrated that preoperative neutrophil count was a strong independent prognostic factor for OS and RFS after adjusting for clinical and pathologic characteristics.…”
Section: Discussionmentioning
confidence: 99%